2023
DOI: 10.25077/jsfk.9.3.227-236.2022
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Rasionalitas Penggunaan Antibiotik pada Beberapa Rumah Sakit di Indonesia: Kajian Literatur Mengenai Kualitas dan Tantangannya

Abstract: Meningkatnya kejadian resistansi antibiotik menyebabkan terbatasnya pilihan terapi antibiotik, sehingga berdampak terhadap morbiditas dan mortalitas pasien. Untuk mengendalikan resistansi antibiotik, maka dikeluarkan Peraturan Menteri Kesehatan (Permenkes) No.8 Tahun 2015 tentang Program Pengendalian Resistansi Antimikroba (PPRA) di rumah sakit yang diharapkan dapat memperbaiki penggunaan antibiotik baik secara kuantitatif maupun kualitatif. Kajian literatur ini bertujuan untuk mengetahui evaluasi penggunaan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The results of the character study of the use of prophylactic antibiotics according to the dose of prophylactic antibiotics based on table 8 showed that the distribution of prophylactic Antibiotic doses < 1000 mg was 6.9%, 1000-1999 mg was 48.9%, 2000-2999 mg was 43.4% and 3000 mg as much as 0.8% so that it was concluded that patients with surgery were given a maximum dose of 1000-1999 mg (Sadli et al, 2023). According to the recommendations of the surgical Antibiotic Prophylaxis Guidelines, the recommended adult dose is given as much as 2g (adults BW 120 kg: 3 g) if the patient data results according to body weight are <50 Kg as much as 9.3%, 50-120 Kg as much as 90.7% and > 120 kg as much as 0% so that it can be concluded that the maximum body weight is 50-120 kg with a dose of Prophylactic Antibiotics given 2 g and body weight > 120 kg as much as 0%, there should be no patient receiving a dose of Prophylactic Antibiotics > 3 g.…”
Section: Prophylactic Antibiotic Dosagementioning
confidence: 99%
“…The results of the character study of the use of prophylactic antibiotics according to the dose of prophylactic antibiotics based on table 8 showed that the distribution of prophylactic Antibiotic doses < 1000 mg was 6.9%, 1000-1999 mg was 48.9%, 2000-2999 mg was 43.4% and 3000 mg as much as 0.8% so that it was concluded that patients with surgery were given a maximum dose of 1000-1999 mg (Sadli et al, 2023). According to the recommendations of the surgical Antibiotic Prophylaxis Guidelines, the recommended adult dose is given as much as 2g (adults BW 120 kg: 3 g) if the patient data results according to body weight are <50 Kg as much as 9.3%, 50-120 Kg as much as 90.7% and > 120 kg as much as 0% so that it can be concluded that the maximum body weight is 50-120 kg with a dose of Prophylactic Antibiotics given 2 g and body weight > 120 kg as much as 0%, there should be no patient receiving a dose of Prophylactic Antibiotics > 3 g.…”
Section: Prophylactic Antibiotic Dosagementioning
confidence: 99%